An evaluation of the application of a TiO2/ Cu(II)/solar simulated radiation system for selective oxidation of benzyl alcohol derivatives. Issue 5 (28th August 2012) - Marotta, Raffaele; Di Somma, Ilaria; Spasiano, Danilo; Andreozzi, Roberto; Caprio, Vincenzo
Abstract BACKGROUND: The conversion of hydroxybenzyl alcohols, nitro‐benzyl alcohol and methoxybenzyl alcohols into the corresponding aldehydes is attempted in aqueous solution by Cu(II) (which reduces to Cu(0)), at room temperature, under acidic and deaerated conditions, using TiO2 solar simulated light photocatalysis. RESULTS: Under the experimental conditions adopted, the yields of the corresponding hydroxyaldehydes, when Cu(II) was completely reduced to Cu(0), were 21.6% for 4‐hydroxybenzaldehyde, 11.5% for 3‐hydroxybenzaldehyde and 20.2% for 2‐hydroxybenzaldehyde. Higher conversions of 2‐methoxybenzyl alcohol and 4‐methoxybenzyl alcohol were recorded relative to unsubstituted benzyl alcohol. A selectivity of 5.2%, at 50% conversion of the substrate, was observed for the oxidation of 4‐nitrobenzyl alcohol to 4‐nitrobenzaldehyde. For high degrees of aromatic alcohols conversion, oxidation of the generated aldehydes to the corresponding benzoic acid derivatives is observed. CONCLUSION: The introduction of substituents into the aromatic alcohols structure changes the photocatalytic oxidation rate and product selectivities with respect to that previously observed for unsubstituted benzyl alcohol. In particular, the presence of both electron donating (hydroxy, methoxy groups) and electron withdrawing (nitrogroup) groups on the aromatic ring of the substrate causes a detrimental effect on the selectivity of the process with respect to the case of benzyl alcohol. © 2012 Society of Chemical Industry